FRI0480 SCHNITZLER'S SYNDROME: DESCRIPTION OF AN ITALIAN MULTICENTER COHORT. (2nd June 2020) - Crisafulli, F.; Airò, P.; Franceschini, F.; Tincani, A.; Frassi, M.
Abstract : Background: Schnitzler's syndrome is an autoinflammatory disease characterized by monoclonal gammopathy and recurrent episodes of urticaria accompanied by clinical and laboratory signs of acute inflammation. Although the exact pathogenic mechanisms have not been fully clarified, the role of Interleukin-1 seems to be central. Objectives: To describe clinical features and therapeutic approach in patients with Schnitzler's Syndrome. Methods: Retrospective analysis of an Italian multicenter cohort. Data are expressed as the median (IQR). Results: The clinical data of 24 patients from 9 centers (median follow-up 6 years [2-10]; median age at diagnosis 56.5 years [51.25-64.25]) were collected. The median diagnostic delay was 2 years (0-10); the diagnosis was made consensually at the onset of symptoms in 4 cases. The main clinical and laboratory features are shown in Table 1 . Therapeutic response was evaluable in 20 patients: all received corticosteroids (CS; 25mg/day [25-50]); in one case, a good clinical response was observed. Eight patients were initially treated with colchicine: in 3 cases it was effective in controlling symptoms and reducing the dose of CS; other 8 patients were treated with csDMARDs (n:1 [1-2]): only 1 patient had a good response to cyclosporin. A bDMARD was initiated in 15 patients. In 7 of the 14 patients initially treated with anakinra this therapy was continued with benefit whereas in the other 7 patients the treatment was discontinued for primary inefficacy (1 patient), secondary inefficacy (3 patients) and adverse events (3 patients; 2 injection site reaction, 1 severe allergic reaction). After anakinra discontinuation, 5 patients were treated with canakinumab with a good response in 3 cases and a partial response in 1 case (persistent arthritis); 1 patient died during the treatment. No response was observed in 3 patients treated with TNF inhibitors as a 2 nd or 3 rd line bDMARDs, as well as in 1 case initially treated with tocilizumab (in which a good response was afterwards obtained with canakinumab). bDMARDs were associated with a csDMARD in 2 patients (methotrexate and methotrexate + cyclosporine). In one case monoclonal gammopathy evolved into Multiple Myeloma and the patient died 15 years after the onset of symptoms. Idiopathic myelofibrosis and myelodysplasia were found in one and in two patients, respectively. Conclusion: In most cases csDMARDs and bDMARDs like anti-IL6 and anti-TNFα were not able to control the disease. In contrast, in some cases, a good response to colchicine was observed; refractory patients may be successfully treated with anti-IL1 agents. Patients should be supervised for possible evolution towards lymphoproliferative disease. Disclosure of Interests: None declared